The grasping process in problem solving of selected high school students - Natividad, Tita Salcedo (Animo Repository, 2003)
Ten fourth year high school students were asked to make a written translation and solution to ten non-routine word problems. The same students were interviewed to enable them to explain their understanding about the word problems and their solutions. The students quality of grasping was investigated based on the written translation and solution strategy. The quality of grasping demonstrated by the students was classified as grasping with understanding, incomplete grasping, and prothetic grasping. Questions asked during the interview focused on the first phase of problem solving which is understanding the problem or what is known as the grasping process. The quality of grasping based on the translation of the problem was generally consistent with the quality of grasping based on the solution strategy of the student-participants in this study. Students experience difficulty in mathematics, particularly in solving word problems because of poor language comprehension. This is true even among students with average to superior grasping ability and these difficulty is experienced in greater magnitudes and with greater frequency by students with poor to below-average grasping ability. This study recommends the following: that problem solving instruction should focus on the grasping process, even if it means using the first language or dialect in building math concepts, that teachers should design contextual problems with a readability suited to the reading ability of the students, and for reading and writing to be part of mathematics instruction to train students to use language as a tool rather than as a barrier to problem solving.